Impact of Dental Treatment Simulation App on Anxiety of Pediatric Dental Patients: An Observational Study - S. K. Mahboob Rahaman; Niladri Maiti; Sonali Harish; Mahantesh Achanur; Michael S. Pramanik; Adnan Ahmed (Journal of Pharmacy and Bioallied Sciences)
Aim: The study aimed to investigate the effect of a dental treatment simulation app on the anxiety levels of pediatric dental patients. Materials and Methods: Forty children, aged 4–8 years and with no prior dental experience, were randomly assigned to either the control group (group I) or the dental app group (group II). The children’s anxiety levels were measured before and after undergoing restorative dental treatment, using the Chota Bheem Chutki pictorial scale. Results: The initial anxiety levels were similar across both groups. Post treatment, the dental app group exhibited a significant reduction in anxiety compared to the control group. This suggests that the simulation app has a beneficial effect in lowering dental anxiety in children. Conclusion: The dental treatment simulation app can effectively reduce pre and postoperative anxiety in pediatric patients, potentially enhancing their overall dental experience.